Physicochemical Characterization of an Exopolysaccharide Produced by Lipomyces sp. and Investigation of Rheological and Interfacial Behavior - Wentian Li; Yilin Guo; Haiming Chen; Wenxue Chen; Hailing Zhang; Ming Zhang; Qiuping Zhong; Weijun Chen (Gels, 2021)
The present study aimed to evaluate the rheological and interfacial behaviors of a novel microbial exopolysaccharide fermented by L. starkeyi (LSEP). The structure of LSEP was measured by LC-MS, 1H and 13C NMR spectra, and FT-IR. Results showed that the monosaccharide composition of LSEP was D-mannose (8.53%), D-glucose (79.25%), D-galactose (7.15%), and L-arabinose (5.07%); there existed the anomeric proton of α-configuration and the anomeric carbon of α- and β-configuration; there appeared the characteristic absorption peak of the phosphate ester bond. The molecular weight of LSEP was 401.8 kDa. The water holding capacity (WHC, 2.10 g/g) and oil holding capacity (OHC, 12.89 g/g) were also evaluated. The results of rheological properties showed that the aqueous solution of LSEP was a non-Newtonian fluid, exhibiting the shear-thinning characteristics. The adsorption of LSEP can reduce the interfacial tension (11.64 mN/m) well and form an elastic interface layer at the MCT–water interface. Such functional properties make LSEP a good candidate for use as thickener, gelling agent, and emulsifier to form long-term emulsions for food, pharmaceutical, and cosmetic products.